2022
DOI: 10.3390/agronomy12112790
|View full text |Cite
|
Sign up to set email alerts
|

Plant Immunity Is Regulated by Biological, Genetic, and Epigenetic Factors

Abstract: An immune system is a protective mechanism that shields plants from environmental stresses. This primary function is to maintain optimal circumstances for the growth and development of plant tissues while avoiding harm from biotic and abiotic stress factors. Plants subjected to various stressors initiate stress signaling cascades that affect multiple gene expressions and induce adaptation. These signaling pathways are coordinated by transcription factors, non-coding RNAs, RNA-binding proteins, and protein–prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 255 publications
0
1
0
Order By: Relevance
“…However, there are substantial differences in the outcomes of these impacts on plants at different growth stages. Research has shown that under MNP stress, plants initiate various gene expression responses and induce adaptive stress signaling cascades across different growth stages and tissue types [71]. Specifically, during the vegetative stage, MNP primarily suppress the expression of genes encoding nitrate transporters in plant roots and genes involved in photosynthesis, inhibiting the nutritional growth of plants.…”
Section: The Impact On Plant Gene Expression and Geneticsmentioning
confidence: 99%
“…However, there are substantial differences in the outcomes of these impacts on plants at different growth stages. Research has shown that under MNP stress, plants initiate various gene expression responses and induce adaptive stress signaling cascades across different growth stages and tissue types [71]. Specifically, during the vegetative stage, MNP primarily suppress the expression of genes encoding nitrate transporters in plant roots and genes involved in photosynthesis, inhibiting the nutritional growth of plants.…”
Section: The Impact On Plant Gene Expression and Geneticsmentioning
confidence: 99%